Direct vascular channels connect skull bone marrow and the brain surface enabling myeloid cell migration. (September 2018) - Herisson, Fanny; Frodermann, Vanessa; Courties, Gabriel; Rohde, David; Sun, Yuan; Vandoorne, Katrien; Wojtkiewicz, Gregory; Masson, Gustavo; Vinegoni, Claudio; Kim, Jiwon; Kim, Dong-Eog; Weissleder, Ralph; et al.
Abstract Innate immune cells recruited to inflammatory sites have short life spans and originate from the marrow, which is distributed throughout the long and flat bones. While bone marrow production and release of leukocyte increases after stroke, it is currently unknown whether its activity rises homogeneously throughout the entire hematopoietic system. To address this question, we employed spectrally resolved in vivo cell labeling in the murine skull and tibia. We show that in murine models of stroke and aseptic meningitis, skull bone marrow-derived neutrophils are more likely to migrate to the adjacent brain tissue than cells that reside in the tibia. Confocal microscopy of the skull–dura interface revealed myeloid cell migration through microscopic vascular channels crossing the inner skull cortex. These observations point to a direct local interaction between the brain and the skull bone marrow through the meninges. The authors describe microscopic channels that directly connect the skull marrow cavities with the meninges. Neutrophils originating from the skull marrow have a higher propensity to travel to the ischemic mouse brain than cells in the tibia.